Development and proof of concept of a blended physiotherapeutic intervention for patients with non-specific low back pain. Issue 4 (December 2019) - Kloek, C.J.J.; van Tilburg, M.L.; Staal, J.B.; Veenhof, C.; Bossen, D.
Abstract: Objective: To develop a blended physiotherapeutic intervention for patients with non-specific low back pain (e-Exercise LBP) and evaluate its proof of concept. Design: Focus groups with patients, physiotherapists, and eHealth and LBP experts were conducted to investigate values according to the development of e-Exercise LBP. Proof of concept was evaluated in a multicentre study. Setting: Dutch primary care physiotherapy practices ( n = 21 therapists). Participants: Adults with non-specific LBP ( n = 41). Intervention: e-Exercise LBP was developed based on clinical LBP guidelines and the focus groups, using the Center for eHealth Research Roadmap. Face-to-face physiotherapy sessions were integrated with a web application consisting of 12 information lessons, video-supported exercises and a physical activity module with the option to gradually increase individuals' level of physical activity. The intervention could be tailored to patients' risk of persistent disabling LBP, according to the STarT Back Screening Tool. Main outcome measures: Functional disability, pain, physical activity, sedentary behaviour and fear-avoidance beliefs, measured at baseline and 12 weeks. Results: After 12 weeks, improvements were found in functional disability [Quebec Back Pain Disability Scale: mean difference (MD) −12.2/100; 95% confidence interval (CI) 8.3 to 16.1], pain (Numeric Pain Rating Scale: MD −2.8/10; 95% CI 2.1 to 3.6), subjective physical activity (Short Questionnaire to Assess Health Enhancing Physical Activity: MD 11.5 minutes/day; 95% CI −47.8 to 24.8) and objective sedentary behaviour (ActiGraph: MD −23.0 minutes/day; 95% CI −8.9 to 55.0). Small improvements were found in objective physical activity and fear-avoidance beliefs. The option to gradually increase physical activity was activated for six patients (15%). On average, patients received seven face-to-face sessions alongside the web application. Conclusions: The results of this study provide the first indication of the effectiveness of e-Exercise LBP, particularly for disability and pain among patients with LBP. Future studies will focus on end-user experiences and (cost-) effectiveness.